resolve o gráfico
y=-x+4 fazer gráfico
Soluções para a tarefa
Respondido por
2
Vamos lá
Resolução :
Y = - X + 4
f ( - 2 ) = - ( - 2 ) + 4
f ( - 2 ) = 2 + 4
f ( - 2 ) = 6
f ( - 1 ) = - ( - 1 ) + 4
f ( - 1 ) = 1 + 4
f ( - 1 ) = 5
f ( 0 ) = - ( 0 ) + 4
f ( 0 ) = 4
f ( 1 ) = - ( 1 ) + 4
f ( 1 ) = 3
f ( 2 ) = - ( 2 ) + 4
f ( 2 ) = 2
Resolução :
Y = - X + 4
f ( - 2 ) = - ( - 2 ) + 4
f ( - 2 ) = 2 + 4
f ( - 2 ) = 6
f ( - 1 ) = - ( - 1 ) + 4
f ( - 1 ) = 1 + 4
f ( - 1 ) = 5
f ( 0 ) = - ( 0 ) + 4
f ( 0 ) = 4
f ( 1 ) = - ( 1 ) + 4
f ( 1 ) = 3
f ( 2 ) = - ( 2 ) + 4
f ( 2 ) = 2
Anexos:
![](https://pt-static.z-dn.net/files/dbc/33abd899fe870c32f7f3fed518be306d.jpg)
Perguntas interessantes